EFEKTIFITAS PELAYANAN IZIN MENDIRIKAN BANGUNAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA MANADO - SUWIGNYA, JUNIAR; DENGO, SALMIN; POMBENGI, JERICHO (Sam Ratulangi University, 2018)
Abstract: This study aims to explain the effectiveness of building permit services at the One Stop Investmentand One Stop Service (DPMPTSP) in Manado City in order to improve public services to the public. Theeffectiveness of building permit services is a means to measure the success of service on DPMPTSP inManado which refers to the applicable regulations. The licensing service is carried out by DPMPTSP ofManado City based on Manado's mayoral regulation No. 4 year 2017 on licensing and non-licensing inDPMPTSP Manado City. This research uses descriptive method of qualitative approach, and data collectiontechnique done by observation, interview technique and documentation. Number of informants as many as 8people. In this research, the effectiveness measurement is seen from the process approach according to Lubisand Huseini, where in this process approach include 5 indicators as follows (i) service efficiency, (ii) serviceprocedure, (iii) employee responsiveness, (iv) Coordination between leadership and subordinates, (v) facilitiesand infrastructure. The result of the research shows that the building permit service at DPMPTSP of ManadoCity is not yet maximal or not yet effective, this can be seen in the settlement of the construction permit whichis not on time, inadequate workspace infrastructure, the lack of technical team resulted in more workload,and there is still a lack of clarity in the procedures for maintaining the building.Keywords: Effectiveness, Service, Building Permit